Análise de diversidade genética em Cattleya forbesii (Lindley) (Orchidaceae) propagadas in vitro - Kuhn, Betty Cristiane (2011)
The purpose of the present study was to establish the Touch Down RAPD (td-RAPD) methodology to investigate the genetic diversity of Cattleya forbesii seedlings obtained from seeds germinated in vitro. It is possible that the wide genetic variability naturally described in studies analyzing populations distributed in their natural habitats, could also be observed in seedlings of C. forbesii grown from seeds germinated in vitro. In the td-RAPD, the PCR program was adjusted, in which theannealing temperature was modified in relation to conventional PCR. A 42°C was used for the initial annealing temperature, from which the temperature decreased 0.5°C after each cycle, until the 37°C was achieved and maintained in the following cycles. From the 82 tested primers, twelve (OPB17, OPB18, OPC02, OPC05, OPC06, OPC07, OPC08, OPC19, OPM02, OPM03, OPM05 and OPP08) were chosen to amplify 43 DNA samples of C. forbesii seedlings produced by seeds germinated KC medium. The polymorphism among C. forbesii plants was 89.19%. The primer that showed less polymorphism (64.28%) was the OPM02, with 14 bands from which five were monomorphic. The OPC02 primer generated a larger number of fragments, a total of 17 fragments, all being polymorphic; the OPC02, OPC07, OPC08, OPC19 and OPM03 showed 100% of polymorphic bands. The genetic base of the seedlings grown from seeds germinated in vitro using KC medium was wide (0.50 to 0.86), indicating that the in vitro growth can produce seedlings with large genetic variability. The germination and in vitro growth system of C. forbesii seeds didn't established a selection pressure that could indicate a reduction in the genetic diversity of the specie. This system can be considered appropriate to produce seedlings for the replenishment of stocks to be grown in the wild, or with the perspective of executing assortative mating to stimulate the production of hybrids.